Historical experience and historicity of the experience: the world as hermeneutical space (ALPHA. Journal of Arts, Literature and Philosophy, 2018)
The following article aims at showing the mutual correspondence between experience and historicity in the work of Hans-Georg Gadamer. Experience is understood as the fundamental movement of the historical existence, which articulates the various spheres of human action. The hermeneutic experience shows that understanding does not lie in a methodical procedure, but in the way of existence in the world. The hermeneutic act is understood as a continuing appropriation process that is carried out through language and where new meanings are updated, that reveal the mobile characteristics of the interpretation. Therefore, the historicity of understanding is the fundamental hermeneutical principle which excludes the possibility of an absolute historical consciousness, in favor of a historically-effected consciousness (wirkungsgeschtliches Bewußtseins).
Keywords: Hermeneutic; Experience; Historicity; History of Effect and Gadamer